The Emotional Life of Your Brain : How Its Unique Patterns Affect the Way You Think, Feel, and Live - and How You Can Change Them /: How Its Unique Patterns Affect the Way You Think, Feel, and Live - and How You Can Change Them. (2012) - Begley, Sharon; Davidson, Richard
No abstract available